Severe distal cytomegalovirus esophagitis with aerodigestive symptoms in an immunocompetent infant - Machado, Nilton Carlos [UNESP]; Carvalho, Mary de Assis [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Elmer Press, 2013)
We report a case of an immunocompetent infant, with no evidence of neurological disorders, which developed clinical manifestation of recurrent crisis of choking, dysphagia, laryngeal stridor and sub costal retractions since the first day of life. Direct laryngoscopy was unremarkable. Upper gastrointestinal series showed a dilated tortuous esophagus with severe peristalsis impairment and reflux episodes till the proximal third of the esophagus. An upper gastrointestinal endoscopy showed a moderately dilated esophagus with erosive lesions in the distal esophagus. Esophageal biopsy specimens revealed CMV inclusion bodies associated to moderate inflammation and immunohistochemistry was positive for CMV early antigen. Prolonged 24 h esophageal pH metry was within normal limits. Antiviral therapy with intravenous ganciclovir was introduced and was associated with rapid improvement of the symptoms. Child gradually increased oral intake and weight gain, and there were no side effects related to therapy. Thus, the respiratory symptoms could have been a supra esophageal manifestation of a non-acid reflux disease related to the CMV esophagitis.
Keywords: Cytomegalovirus; Esophagitis; Ganciclovir; Immunocompetent infant; Immunohistochemistry